Transient hypogammaglobulinemia of infancy with no evidence of immunodeficiency other than atopic dermatitis: A case report and review of literature. Issue 5 (25th November 2018) - Minowa, Tomoyuki; Sumikawa, Yasuyuki; Hida, Tokimasa; Uhara, Hisashi
Abstract : We report an infant with transient hypogammaglobulinemia of infancy (THI) who had severe atopic dermatitis (AD), but showed no history of infections. The lack of history of infections poses a risk that the underlying THI may be overlooked because most infants with THI are identified due to the history of infections. Our aim was to carefully delineate the clinical presentations of THI‐associated AD and normal AD through a case report and review of previous literature. Our findings suggest that the history of infections may be an infrequent presentation among patients with THI‐associated AD.